Efektivitas Penggunaan Media Interaktif Berbasis PowerPoint dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - Lolita Yulis Pusvita (Journal of Elementary Education Research, 2026)
Language learning is not merely the acquisition of grammatical knowledge but also the development of communicative competence within social contexts. In elementary schools, Indonesian language instruction often emphasizes structural aspects, while pragmatic and sociocultural dimensions receive limited attention. The integration of interactive PowerPoint-based media offers opportunities to contextualize language use, promote authentic discourse analysis, and foster students’ communicative awareness.This study aims to examine the effectiveness of interactive PowerPoint-based media in Indonesian language learning, particularly in integrating sociolinguistic principles to enhance students’ communicative competence.This research employed a descriptive qualitative design with a literature review approach. Data were collected through systematic searches of academic documents (journal articles, books, and conference proceedings) from databases such as Google Scholar. The collected sources were analyzed using thematic content analysis to identify recurring concepts, implementation models, and key findings.The findings indicate that interactive PowerPoint media can facilitate authentic discourse analysis, role-play simulations, and discussions on language variation and politeness strategies. Such approaches positively influence students’ understanding of language variation, register, context-appropriate language use, pragmatic awareness, and sociocultural competence.Sociolinguistic-based interactive learning through PowerPoint serves as a bridge between linguistic knowledge and real-life communication skills, preparing students to engage effectively in diverse social contexts.